Leading STEM Success: The Role of School Principals in Advancing Science and Mathematics Through Instructional Leadership - Arokiasamy, Anantha Raj A.; Tasaloti, Mehdi; Ngadiron, Ms. Suhaila; Hossain, Syed Far Abid; Tanucan, Jem Cloyd M. (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the roles and responsibilities of school principals in fostering effective science and mathematics instruction through the lens of Instructional Leadership. Given the critical role of quality education, particularly in science and mathematics, this research aligns with Sustainable Development Goal 4 (SDG 4) on quality education. It explores how school principals create opportunities for effective teaching and learning within their schools. A qualitative case study approach was employed to gain in-depth insights into leadership practices. Data were collected through unstructured interviews with thirteen participants across six Malaysian public schools. This method allowed for a detailed exploration of the ways principals facilitate instructional improvements in science and mathematics. The study reveals that school principals act as instructional leaders, subject specialists, and classroom experts, ensuring accountability for student performance. Their leadership extends beyond administrative duties, directly influencing instructional practices by supporting teachers and implementing structured leadership strategies. This highlights the pivotal role of principals in shaping educational outcomes in science and mathematics. The findings underscore the significance of Instructional Leadership in improving curriculum implementation and teaching quality in science and mathematics. School principals play a crucial role in guiding educators, fostering collaborative learning environments, and enhancing student achievement. Given the multifaceted nature of school leadership, further research is recommended to explore how principals navigate their instructional responsibilities in different educational settings. Understanding these dynamics could inform policy decisions and professional development programs aimed at strengthening Instructional Leadership in diverse school environments.